Air separation with cryogenic energy storage: Optimal scheduling considering electric energy and reserve markets - Zhang, Qi; Grossmann, Ignacio E.; Heuberger, Clara F.; Sundaramoorthy, Arul; Pinto, Jose M. (AIChE journal, 2015)
The concept of cryogenic energy storage (CES) is to store energy in the form of liquid gas and vaporize it when needed to drive a turbine. Although CES on an industrial scale is a relatively new approach, the technology is well known and essentially part of any air separation unit that utilizes cryogenic separation. In this work, the operational benefits of adding CES to an existing air separation plant are assessed. Three new potential opportunities are investigated: (1) increasing the plant's flexibility for load shifting, (2) storing purchased energy and selling it back to the market during higher‐price periods, and (3) creating additional revenue by providing operating reserve capacity. A mixed‐integer linear programming scheduling model is developed and a robust optimization approach is applied to model the uncertainty in reserve demand. The proposed model is applied to an industrial case study, which shows significant potential economic benefits. © 2015 American Institute of Chemical Engineers AIChE J, 61: 1547–1558, 2015